Management analysis in the collection, processing and destination of recyclable waste in the capital district in the period 2019 - 2021 (2021)
In the Colombian capital there is the absence of a defined and well structured recycling system, currently private companies are in charge of carrying out this task where their main activity is the purchase of recyclable material, it is then where the work of the recyclers who are directly in charge of separating usable waste, discarding those that cannot return to the production cycle and could no longer have value, when collecting all those useful materials they are transported through different types of means and taken to warehouses or recycling plants where They are in charge of making classifications to weigh the elements and sell them to companies. Companies or people who recycle on a small or large scale that have a great variation in tactics either manually or applying technology depending on the type of material and technique applied to recycle since there is chemical, energy and mechanical recycling. Likewise, the types of recycling by material stand out, be it recycling of paper, plastic, glass, textiles, and footwear, organic, cells and batteries, scrap metal, debris, electronic devices and water. All these materials in mention have a different handling in the collection, transport, and process. The current way of recycling in the capital district is exposed where a differentiation of recyclable waste is made through a color code, the different tools and more advanced technologies that can be used to improve the recycling process are also pointed out, doing it in an efficient and safe. Among the best known tools are ChatBot, ContainerGo, SmartWaste, plant 4.0, big data, the circular economy, and the manufacture of sustainable packaging.